Performance of the physiotherapist in urgency and emergency: reality of professionals and graduates from the Integrated Multiprofessional Residence Program (Research, Society and Development, 2023)
Objectives: Identify the profile of two professional physiotherapists in the Urgência and Emergência units and in the hospital environment and assess the impact of the Multiprofessional Residency on the professional life of two discharged residents. Materials and Methods: Research with a quantitative approach, of a descriptive nature, through a questionnaire to identify the reality of the physiotherapy team in the Urgency and Emergency and in the hospital environment, as well as the reality of graduates of the Residency Program Integrated Multiprofessional Care in Urgency and Emergency. Results and discussion: 46 professionals participated in this research, mostly white women, specialists, with 10 years or more of training and hospital experience. Most professionals are called on to perform functions that are not exclusive to physiotherapy and little called on to perform private activities such as kinesiotherapy. Regarding the graduates, everyone believes that the completion of the Residency had a positive impact on their professional career. Conclusion: In the entire hospital environment, physical therapists are being called by the team for acute conditions, especially in respiratory issues, behaviors that are not exclusive to the profession. The Multiprofessional Residency brings in its entirety positive impacts on the professional career of graduates and the guarantee of work, as all graduates are employed.